GE_GERICHTE P/19735/2006 vom 12. September 2008 - GE Cour de justice (2008)
; LÉSION CORPORELLE ; MENACE(DROIT PÉNAL) ; SURSIS À L'EXÉCUTION DE LA PEINE ; LÉGITIME DÉFENSE ; TORT MORAL | CP.180; CP.15; CP.47; CP.42; CP.43; CP.122; CP.123.2; CO.47; CO.42